Patients with unilateral transfemoral amputation treated with a percutaneous osseointegrated prosthesis: a cost-effectiveness analysis. (April 2018) - Hansson, E.; Hagberg, K.; Cawson, M.; Brodtkorb, T. H.
Abstract : Aims: The aim of this study was to compare the cost-effectiveness of treatment with an osseointegrated percutaneous (OI-) prosthesis and a socket-suspended (S-) prosthesis for patients with a transfemoral amputation. Patients and Methods: A Markov model was developed to estimate the medical costs and changes in quality-adjusted life-years (QALYs) attributable to treatment of unilateral transfemoral amputation over a projected period of 20 years from a healthcare perspective. Data were collected alongside a prospective clinical study of 51 patients followed for two years. Results: OI-prostheses had an incremental cost per QALY gained of €83 374 compared with S-prostheses. The clinical improvement seen with OI-prostheses was reflected in QALYs gained. Results were most sensitive to the utility value for both treatment arms. The impact of an annual decline in utility values of 1%, 2%, and 3%, for patients with S-prostheses resulted in a cost per QALY gained of €37 020, €24 662, and €18 952, respectively, over 20 years. Conclusion: From a healthcare perspective, treatment with an OI-prosthesis results in improved quality of life at a relatively high cost compared with that for S-prosthesis. When patients treated with S-prostheses had a decline in quality of life over time, the cost per QALY gained by OI-prosthesis treatment was considerably reduced. Cite this article: Bone Joint J 2018;100-B:527–34.